Virtual Reality-Based Exercise with Exergames as Medicine in Different Contexts: A Short Review - Costa, Marcos Túlio Silva; Vieira, Lanna Pinheiro; Barbosa, Elizabete de Oliveira; Mendes Oliveira, Luciana; Maillot, Pauline; Otero Vaghetti, César Augusto; Giovani Carta, Mauro; Machado, Sérgio; Gatica-Rojas, Valeska; Monteiro-Junior, Renato Sobral (Clinical practice and epidemiology in mental health, 2019)
There is enough evidence that, nowadays, the sedentary lifestyle is one of the major health problems worldwide, linked to many chronic diseases, including mental comorbidities, systemic hypertension, metabolic dysregulation, and cancer. Although health societies recommend engagement to physical activities, there is an overwhelming number of people remaining sedentary, even knowing the health benefits of regular exercises. One of the main factors that justifies this scenario is the lack of motivation, which is a barrier to people intended to start new habits for health. Considering this previous information, new alternatives for exercises may help people engage in a healthier lifestyle. Technology has contributed to this with devices that allow movements based on virtual reality approaches, including the exergames. These are games available even in commercial devices, as video-games, that allow people to work with different physical components. Furthermore, exergames add cognitive gain through its dual-task characteristic. Moreover, due to the combination of these benefits, they are feasible to acquire, and easy to use. Exergames are not only a potential strategy to reduce sedentary lifestyle but also a good method to improve health gains and rehabilitation in different populations and pathological conditions: older adults, stroke survivors, and Parkinson’s disease. In this review, we aim to demonstrate some conditions that literature supports the intervention with exergames due to its physical and cognitive benefits. Furthermore, at the end of this review, we also explore the neurobiological mechanisms behind virtual-reality based exercises.